2014
DOI: 10.1002/jrs.4494
|View full text |Cite
|
Sign up to set email alerts
|

Determination of degree of unsaturation in edible oils using coherent anti‐Stokes Raman scattering spectroscopy

Abstract: We demonstrate the use of coherent anti-Stokes Raman scattering (CARS) spectroscopy for determination of degree of unsaturation in edible oils. To this end, we have measured CARS spectra of six kinds of commercial edible oils having different degree of unsaturation, and it was found that the spectral intensity ratio (I ¼C-H /I C-H ) of two specific bands in C-H stretch region depends on the degree of unsaturation of sample. Based on this relation, the mass unsaturation (N ¼C-H /N C-H ) of six oils was estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…PA and SA have carbon–carbon single bonds with 16 carbons and 18 carbons within the fatty acid chain, respectively. However, OA, LA, and LNA having 18 carbons contain one, two, and three double bonds within the fatty acid chain, respectively …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…PA and SA have carbon–carbon single bonds with 16 carbons and 18 carbons within the fatty acid chain, respectively. However, OA, LA, and LNA having 18 carbons contain one, two, and three double bonds within the fatty acid chain, respectively …”
Section: Resultsmentioning
confidence: 99%
“…In the previous study of our group, the relation between mass unsaturation and CARS intensity ratio of six edible oils and fatty acids was observed. And we demonstrated that CARS spectroscopy can determine the degree of unsaturation in edible oils and obtained the calibration curve for determining iodine value that can be an alternative method of existing chemical methods . This method can be applied to only pure edible oils.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations